Mesoporous alumina : A comprehensive review on synthesis strategies, structure, and applications as support for enhanced H2 generation via CO2-CH4 reforming - Mahadi, Bahari; Che Rozid, Mamat; Aishah, Abdul Jalil; Nurul Sahida, Hassan; Nabgan, Walid; Herma Dina, Setiabudi; Vo, Dai Viet N.; Phuong Thuy, Bui Thi (Elsevier Ltd, 2022)
Lately, the generation of hydrogen out from carbon dioxide (CO2) - methane (CH4) reforming has been touted as a feasible option for reducing two of the most harmful greenhouse gases (CO2 and CH4) in the atmosphere. However, this technology typically suffered from catalyst deactivation triggered by sintering and coke deposition. Therefore, designing a feasible catalyst by making efficient support selections is vital for overcoming this challenge. Mesoporous alumina (MA) has aroused great attraction attributed to their potential applications as catalysis supports resulted from their high surface areas combined with tunable, narrow, and uniform pore size distribution, as well as their ability to constrain active metal from sintered and deactivated during the reaction. These materials' morphology, composition, and pore structure can be directly tailored during synthesis by altering the synthesis parameters like the type of the surfactants/templates employed, pH conditions, or selection of alumina precursors. As a result, this review's major focus is on synthesizing unique MA using a range of synthesis routes and conditions. Apart from that, this review also focuses on the applications and performance of MA as catalyst support during the CO2-CH4 reforming. We believe that this effort provides the complete grasp of MA contribution towards improving the CO2-CH4 reforming activity.